Crystal structure of 1-benzoyl-2,7-dimethoxy-8-(3,5-dimethylbenzoyl) naphthalene: Head-to-head fashioned molecular motif for accumulating weak non-classical hydrogen bonds - Yokoyama, Takeshi; Mido, Takahiro; Takahara, Genta; Ogata, Kazuki; Chwojnowska, Elżbieta; Yonezawa, Noriyuki; Okamoto, Akiko (European Journal of Chemistry, 2017)
Title compound, 1-benzoyl-2,7-dimethoxy-8-(3,5-dimethylbenzoyl)naphthalene, an unsymmetrically substituted aromatic diketone compound having non-coplanarly accumulated aromatic rings structure, has been synthesized and its crystal structure has been determined by X-ray crystallography. The asymmetric unit of title compound contains two independent conformers. For each conformer, the two aroyl groups are non-coplanarly situated against the naphthalene ring plane and oriented in an opposite direction. The 3,5-dimethylbenzoyl group leans more than the non-substituted benzoyl group on the other peri-position of the naphthalene ring. The characteristics in the single molecular crystal structure of this unsymmetrical compound show unique relationship with two symmetrically substituted homologues, namely 1,8-dibenzoyl-2,7-dimethoxynaphthalene and 2,7-dimethoxy-1,8-bis(3,5-dimethylbenzoyl) naphthalene. Dihedral angles between 3,5-dimethylbenzene ring and naphthalene ring of 2,7-dimethoxy-1,8-bis(3,5-dimethylbenzoyl)naphthalene are larger than those between benzene ring and naphthalene ring of 1,8-dibenzoyl-2,7-dimethoxynaphthalene. Dihedral angle between 3,5-dimethylbenzoyl group and naphthalene ring in title compound is close to those of symmetrical homologue having two 3,5-dimethylbenzoyl groups. In the similar manner, dihedral angle between non-substituted benzoyl group and naphthalene ring in title compound is also close to those of symmetrical homologue bearing two non-substituted benzoyl groups. On the other hand, the crystal packing of title compound has rather similar feature with 2,7-dimethoxy-1,8-bis(3,5-dimethylbenzoyl)naphthalene. Two compounds have common crystalline molecular structural motif of head-to-head fashioned intermolecular interaction of 3,5-dimethylbenzoyl moieties. It is interpreted that the interactions between (sp3)C–H and π orbital preferentially govern the molecular packing motif. Molecular structure feature of title compound and the symmetrically 3,5-dimethylbenzoylated homologue strongly manifests that accumulation of weak non-classical hydrogen bonds play a crucial role in determination of the crystal packing rather than sole function of stronger non-classical hydrogen bond and π…π stacking.